Unleashing the potential of a low CpG Passer transposon for superior CAR-T cell therapy - Zeng, Jianyao; Sun, Yan; Fang, Yuan; Wang, Xiaodie; Huang, Qian; Zhang, Pingjing; Shao, Meiqi; Wang, Pei; Cheng, Jingbo; Di, Meng; Liu, Tao; Qian, Qijun (Frontiers in Immunology, 2025)
BackgroundTo date, the non-viral vector Chimeric Antigen Receptor (CAR) T cell preparation platform, exemplified by transposons, has demonstrated significant potential in tumor immunotherapy and yielded positive results in multiple clinical trials. Nonetheless, non-methylated CpG sequences within plasmid DNA can elicit an inflammatory response via Toll-like receptor 9 (TLR9) during CAR-T cell preparation, adversely affecting transgene expression. Additionally, de novo DNA methylation programs promote T cell exhaustion, which poses a significant limitation for CAR-T cell therapy applications.MethodsHigh-throughput liquid protein chip and CBA analyses were utilized to determine the expression levels of inflammatory factors. Flow cytometry and luciferase reporter assays were employed for mutation screening. BALB/c mice and M-NSG mice were used to evaluate the inflammatory response and efficacy of LCG CAR-T in vivo, with TIL grouping detected via immunohistochemistry.ResultsIn this study, we modified the newly discovered Passer (JL) transposon to construct a low-CpG content transposon for CAR-T cell (LCG CAR-T cell) preparation. In vitro experiments demonstrated that LCG CAR-T cells prepared using this new transposon exhibited stronger cytotoxicity. In animal models, LCG CAR-T cells significantly inhibited tumor growth and increased the populations of CD4+CAR-T cells and tumor-infiltrating lymphocytes. Furthermore, LCG CAR-T cells modulated pro-inflammatory cytokine release, thereby reducing in vivo inflammatory responses and surpassing the effects observed with unmodified CAR-T cells.ConclusionsCollectively, our results demonstrate the high safety and efficacy of non-viral, low CpG Passer transposon CAR-T cells, offering new avenues for improving CAR-T cell efficacy while minimizing in vivo inflammation.